Quantitative business valuation : a mathematical approach for today's professionals - Abrams, Jay B. (John Wiley, 2010)
Praise for the First Edition of Quantitative Business Valuation. A Mathematical Approach for Today's Professionals. "Jay Abrams' book is close to the equivalent of several graduate dissertations rolled into one book. For each topic (covered), he presents a scholarly summary of past research, new empirical research of his own, and his conclusions. It is a well-documented contribution to in-depth understanding of important business valuation issues, and should not be overlooked by the serious practitioner."--Shannon Pratt, DBAManaging Director, Willamette Management AssociatesCoauthor